A method for preparing daylily nanocomposite micropowder with high flavonoid release rate

Through infrasound resonance technology, daylily powder is subjected to inclusion and wall-breaking treatment, which solves the problem of low release rate of flavonoids in daylily, achieves efficient release of flavonoids and improves bioavailability, and promotes the lightweight processing and health care effects of daylily.

CN119523064BActive Publication Date: 2025-04-29ZHEJIANG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510081341.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The release rate of flavonoid active ingredients in daylily is low in the water environment of the human body and is easily lost during the hot processing, making it difficult to exert its health care effects.

Method used

Infrasound resonance technology is used to combine freeze-dried daylily powder with edible auxiliary materials and break the wall to enhance the affinity of daylily powder to water and promote the dissolution of flavonoids.

Benefits of technology

It significantly improves the release rate of flavonoids in aqueous solution, enhances its bioavailability and health care effects, realizes lightweight consumption of daylily, and reduces processing costs and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119523064B_ABST
    Figure CN119523064B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a daylily nano-composite micropowder with a high flavonoid release rate, and the steps are as follows: fresh daylily is freeze-dried and then preliminarily crushed, the freeze-dried daylily is mixed with an auxiliary material and a disintegrant, and subjected to infrasonic resonance treatment, microspheres are used as a force medium in the process, and the mixture subjected to the acoustic resonance treatment is screened to remove large particles, so as to obtain the daylily nano-composite micropowder. The processing process of the invention does not require solvents or the addition of additional chemical reagents, and there is no excessive water content and solvent residue, and the safety is good. Under the action of infrasonic resonance force, the raw materials are ultrafinely crushed and self-emulsified, and the release of flavonoids in the aqueous solution is improved. At the same time, the inclusion material can further react with the insoluble flavonoids in the daylily to form inclusion compounds and intermolecular complexes, improve hydrophilicity, and promote the direct dissolution of effective substances. Therefore, after the treatment, the anti-depression and intestinal motility promoting capabilities thereof are increased, and the purpose of reducing the intake of daylily at the same dose is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food processing, and in particular relates to a method for preparing daylily nano composite micropowder with high flavonoid release rate. Background Art

[0002] The flowers of daylily can be used as vegetables and ornamental plants. The roots have high medicinal value. The edible part is the unopened buds, which are rich in nutrients. Daylily can significantly reduce the level of serum cholesterol, which is beneficial to the recovery of patients with hypertension and can be used as a health vegetable for patients with hypertension. Daylily also contains active ingredients that can inhibit the growth of cancer cells, and the rich crude fiber can promote the excretion of stool, so it can be used as a food for preventing and treating intestinal cancer.

[0003] Studies have found that the main effective ingredients in daylily that have health benefits are flavonoids. These ingredients exist inside cells and have very poor water solubility. Traditional soaking in water or direct consumption has a very low release rate in the water environment in vitro or in vivo. Therefore, a large amount of intake is required to achieve health benefits. In addition, as a food, daylily decomposes and loses a large amount of flavonoids during long-term thermal processing, so it is difficult to exert its excellent health benefits simply by taking it as a food. At present, freeze-drying and other technologies have been used in daylily processing. Although the loss rate of flavonoids has been reduced, its final form cannot be changed, and the release rate of flavonoids is still close to other methods. Therefore, solving the release rate of flavonoids in daylily in the water environment of the human body, changing the way of eating daylily, and achieving lightweight consumption of daylily while ensuring the effect can help solve the dilemma of daylily processing.

[0004] A large number of studies have shown that by preparing a drug delivery system, the solubility of flavonoids insoluble compounds in water environments can be significantly improved. For example, by using disodium glycyrrhizinate as a carrier, the solubility of the flavonoid compound kaempferol in water can be increased by more than 200 times, and the 5-minute release rate can reach 90%, and its hypoglycemic effect has been significantly improved. Using arabinogalactan as a carrier to load seabuckthorn flavonoids, its stability and bioavailability are greatly improved, and its lipid-lowering activity is significantly increased. Using glycyrrhizic acid and arabinogalactanase as carriers to load kaempferol, its bioavailability is increased by more than 2-3 times, and quick-acting release is achieved. Among them, for materials with complex structures and difficult to homogenize, such as food and raw materials, infrasonic resonance solid-phase processing technology is favored. Infrasonic resonance uses the mechanical energy generated by infrasonic vibration to destroy the internal structure of the material, causing it to produce physical and chemical reactions. It uses the high-intensity resonance effect to disperse and grind the plant raw materials and edible auxiliary materials together, while destroying the plant cell wall, promoting the contact and reaction between the effective ingredients and the auxiliary materials, and increasing the solubility of the effective ingredients. It has the advantages of good dispersion effect, unique reaction mechanism, and no need for contact with metals, and meets the standards of food safety and energy conservation and environmental protection. Compared with traditional methods, the steps of infrasonic resonance treatment are relatively simple, no solvent or heating is required, the operation is convenient, the production cycle is short, and the cost is low. The nano-composite micropowder of daylily is processed by infrasonic resonance technology to increase the solubility of flavonoid compounds in body fluids. Thereby improving its effectiveness, it has not been reported yet, which is a major breakthrough in the traditional processing method of daylily, and is of great significance to the realization of high value-added processing of daylily and modernization and efficiency enhancement. Summary of the invention

[0005] In view of the above problems, the object of the present invention is to provide a method for preparing daylily nanocomposite powder with high flavonoid release rate.

[0006] The research idea of ​​the present invention is: according to the chemical structure and properties of day lily flavonoid compounds, the infrasonic resonance inclusion complex is combined with the infrasonic resonance wall-breaking effect to include the freeze-dried day lily powder with edible auxiliary materials, thereby enhancing the affinity of the day lily powder for water and promoting the dissolution of flavonoid compounds, thereby improving the effect of day lily in promoting intestinal peristalsis.

[0007] The specific technical solutions are as follows:

[0008] A method for preparing daylily nano-composite micropowder with high flavonoid release rate is specifically carried out according to the following steps: fresh daylily is subjected to freeze-drying treatment and then initially crushed to 100-200 meshes, freeze-dried daylily powder is mixed with auxiliary materials and disintegrants, subjected to infrasonic resonance treatment using an acoustic resonance mixer, and microspheres are used as a force medium, and then large particles are removed by screening to obtain daylily nano-composite micropowder.

[0009] Furthermore, the auxiliary material is β-cyclodextrin, maltodextrin, arabinogalactan, pectin, maltitol, erythritol, oligofructose, inulin, corn starch or sweet potato starch, preferably oligofructose.

[0010] Furthermore, the mass of the auxiliary materials added accounts for 10% to 90% of the total mass of the raw materials, preferably 50%.

[0011] Furthermore, the disintegrant is one of hydroxypropyl cellulose, microcrystalline cellulose and silica gel powder, preferably hydroxypropyl cellulose, and the added amount is 2-10% of the total mass of the raw materials, preferably 2.5%.

[0012] Furthermore, the material of the acoustic resonance mixer is polytetrafluoroethylene, and zirconium oxide microspheres are used as the force medium. The diameter of the zirconium oxide is 10-25 mm, preferably 15 mm, and the mass ratio of the microspheres to the powder is 1:1-20:1, preferably 10:1.

[0013] Furthermore, the infrasound frequency of the acoustic resonance mixer is 10-40 Hz, preferably 30 Hz; the treatment time is 5-120 min, preferably 30 min.

[0014] The beneficial effects of the present invention are:

[0015] 1) The processing of the present invention does not require solvents or additional chemical reagents, has no excessive moisture or solvent residue, and has good safety;

[0016] 2) The present invention realizes ultrafine grinding of raw materials under the action of infrasonic resonance, improves the release of flavonoids in aqueous solution, and at the same time, the polysaccharides of the day lily itself and the added hydrophilic auxiliary materials can further react with the insoluble flavonoids in the day lily to form self-consistent inclusion compounds and multi-molecular complexes, thereby improving hydrophilicity, promoting direct dissolution of effective substances, and accelerating the rapid release of components. The effective concentration of antidepressants is significantly higher than that of physical mixtures;

[0017] 3) Compared with single crushing, the nanocomposite powder of daylily prepared by infrasound resonance does not require external forces such as shearing or metal contact. The particle size of the powder is greatly reduced while also avoiding excessive metal elements. At the same time, the cell wall is broken by infrasound, the dissolution rate of flavonoids is increased, the dissolution time is shortened, and it is quickly released in the intestine. At the same time, the ability to promote intestinal peristalsis is increased, achieving the purpose of reducing the intake of daylily at the same dose, making it easier to take. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a graph showing the effects of different excipients, disintegrants, excipient addition amounts and disintegrant addition amounts on the release of daylily flavonoids.

[0019] Figure 2This is a graph showing the effects of medium diameter, medium dosage, infrasonic frequency and treatment time on the release of flavonoids from daylily.

[0020] Figure 3 is the dissolution rate of Example 20 and Example 13.

[0021] Figure 4 The following are scanning electron microscope images of the raw material daylily powder and Example 20.

[0022] Figure 5 This is the effect of different treatments on the bright field movement time of zebrafish.

[0023] Figure 6 The effects of different treatments on the fluorescence intensity of zebrafish intestine. DETAILED DESCRIPTION

[0024] The technical scheme of the present invention is described below with specific examples and drawings of the specification, but the protection scope of the present invention is not limited thereto. The daylily used in the embodiment is obtained from fresh daylily that has not bloomed in July and August after freeze-drying, and is identified by relevant experts as a flower of the daylily (Hemerocallis citrina Baroni) of the Asphodelaceae and Hemerocallis genus. The daylily is freeze-dried, crushed, sieved through a 100-mesh sieve, and stored in a cool and dry place for later use.

[0025] Example 1

[0026] The content of total flavonoids in daylily samples was determined by ultraviolet spectrophotometry. First, rutin was used as a standard substance to establish a standard curve for total flavonoid content. The specific method was as follows: 1g of rutin was accurately weighed and placed in a 100ml volumetric flask, and anhydrous ethanol was added to make up the volume as the standard solution. 1ml, 2ml, 4ml, 8ml, and 16ml of the standard solution were accurately measured in a 25ml volumetric flask, 10% aluminum nitrate solution was added 1.0ml, shaken, and made up to volume with distilled water. The solution was left for 30 minutes, and the absorbance value was measured at 384nm with a 1cm colorimetric dish. The standard curve for total flavonoids was established as (Y = 0.5209X + 0.0123, R 2 = 0.9998).

[0027] Example 2

[0028] The total flavonoids content in daylily was determined as follows: 1 g of freeze-dried daylily powder was accurately weighed, and 20 mL of 60% ethanol aqueous solution was added. oC hot reflux extraction for 1h, and then filter and collect the filtrate. The filter residue was extracted twice again according to the above method. The filtrates were combined for three times, and after fine filtration using a nanofiltration membrane, the total flavonoid content in the raw material freeze-dried daylily powder was determined to be 21.12±0.76 mg / g according to the sample determination method described in Example 1. The release rate of flavonoids in daylily was calculated. The flavonoid content c in the sample aqueous solution determined by the method in Example 1, the total flavonoid content of daylily was c0=21.12±0.76 mg / g, and the release rate of flavonoids in daylily was Y (%)=c / c0*100%.

[0029] Example 3

[0030] To a 600 mL polytetrafluoroethylene resonance cavity, 1.0 g of daylily powder, 1.0 g of arabinogalactan, 0.05 g of hydroxypropyl cellulose, and 15 mm diameter zirconia balls were added, and the mass ratio of microspheres to powder was set to 8:1. The mixture was treated at 30 Hz for 30 min. After treatment, the composite powder was taken out, 1 g of the composite micropowder was accurately weighed, 10 mL of water was added, and the mixture was stirred at room temperature for 30 min. The extraction process was repeated 3 times, and the filtrates were combined for 3 times. The total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water were calculated according to the method described in Example 1, and then the release rate of flavonoids in the daylily nano-composite micropowder was calculated.

[0031] Example 4

[0032] To a 600 mL polytetrafluoroethylene resonance cavity, 1.0 g of daylily powder, 1.0 g of β-cyclodextrin, 0.05 g of hydroxypropyl cellulose, and 15 mm diameter zirconia balls were added, and the mass ratio of microspheres to powder was set to 8:1. The mixture was treated at 30 Hz for 30 min. After treatment, the composite powder was taken out, 1 g of the composite micropowder was accurately weighed, 10 mL of water was added, and the mixture was stirred at room temperature for 30 min. The extraction process was repeated 3 times, and the filtrates were combined for 3 times. The total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water were calculated according to the method described in Example 1, and then the release rate of flavonoids in the daylily nano-composite micropowder was calculated.

[0033] Example 5

[0034] To a 600 mL polytetrafluoroethylene resonance cavity, 1.0 g of daylily powder, 1.0 g of maltodextrin, 0.05 g of hydroxypropyl cellulose, and 15 mm diameter zirconia balls were added, and the mass ratio of microspheres to powder was set to 8:1. The mixture was treated at 30 Hz for 30 min. After treatment, the composite powder was taken out, 1 g of the composite micropowder was accurately weighed, 10 mL of water was added, and the mixture was stirred at room temperature for 30 min. The extraction process was repeated 3 times, and the filtrates were combined for 3 times. The total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water were calculated according to the method described in Example 1, and then the release rate of flavonoids in the daylily nano-composite micropowder was calculated.

[0035] Example 6

[0036] To a 600 mL polytetrafluoroethylene resonance cavity, 1.0 g of daylily powder, 1.0 g of maltitol, 0.05 g of hydroxypropyl cellulose, and a zirconia ball with a diameter of 15 mm were added, and the mass ratio of microspheres to powder was set to 8:1. The mixture was treated at 30 Hz for 30 min. After treatment, the composite powder was taken out, 1 g of the composite micropowder was accurately weighed, 10 mL of water was added, and the mixture was stirred at room temperature for 30 min. The extraction process was repeated 3 times, and the filtrates were combined for 3 times. The total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water were calculated according to the method described in Example 1, and then the release rate of flavonoids in the daylily nano-composite micropowder was calculated.

[0037] Example 7

[0038] To a 600 mL polytetrafluoroethylene resonance cavity, 1.0 g of daylily powder, 1.0 g of erythritol, 0.05 g of hydroxypropyl cellulose, and 15 mm diameter zirconia balls were added, and the mass ratio of microspheres to powder was set to 8:1. The mixture was treated at 30 Hz for 30 min. After treatment, the composite powder was taken out, 1 g of the composite micropowder was accurately weighed, 10 mL of water was added, and the mixture was stirred at room temperature for 30 min. The extraction process was repeated 3 times, and the filtrates were combined for 3 times. The total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water were calculated according to the method described in Example 1, and then the release rate of flavonoids in the daylily nano-composite micropowder was calculated.

[0039] Example 8

[0040] To a 600 mL polytetrafluoroethylene resonance cavity, 1.0 g of daylily powder, 1.0 g of oligofructose, 0.05 g of hydroxypropyl cellulose, and 15 mm diameter zirconia balls were added, and the mass ratio of microspheres to powder was set to 8:1. The mixture was treated at 30 Hz for 30 min. After treatment, the composite powder was taken out, 1 g of the composite micropowder was accurately weighed, 10 mL of water was added, and the mixture was stirred at room temperature for 30 min. The extraction process was repeated 3 times, and the filtrates were combined for 3 times. The total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water were calculated according to the method described in Example 1, and then the release rate of flavonoids in the daylily nano-composite micropowder was calculated.

[0041] Example 9

[0042] To a 600 mL polytetrafluoroethylene resonance cavity, 1.0 g of daylily powder, 1.0 g of pectin, 0.05 g of hydroxypropyl cellulose, and 15 mm diameter zirconia balls were added, the mass ratio of microspheres to powder was set to 8:1, and the mixture was treated at 30 Hz for 30 min. After treatment, the composite powder was taken out, 1 g of the composite micropowder was accurately weighed, 10 mL of water was added, and the mixture was stirred at room temperature for 30 min. The extraction process was repeated 3 times, and the filtrates were combined for 3 times. The total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water were calculated according to the method described in Example 1, and then the release rate of flavonoids in the daylily nano-composite micropowder was calculated.

[0043] Example 10

[0044] To a 600 mL polytetrafluoroethylene resonance cavity, 1.0 g of daylily powder, 1.0 g of inulin, 0.05 g of hydroxypropyl cellulose, and 15 mm diameter zirconium oxide balls were added, and the mass ratio of microspheres to powder was set to 8:1. The mixture was treated at 30 Hz for 30 min. After treatment, the composite powder was taken out, 1 g of the composite micropowder was accurately weighed, 10 mL of water was added, and the mixture was stirred at room temperature for 30 min. The extraction process was repeated 3 times, and the filtrates were combined for 3 times. The total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water were calculated according to the method described in Example 1, and then the release rate of flavonoids in the daylily nano-composite micropowder was calculated.

[0045] like Figure 1 As shown in A, various types of polysaccharides as carriers have quite different self-solubilization effects on chrysanthemum flavonoids. The main reason may be that chrysanthemum polysaccharides are more viscous, and using polysaccharides with higher viscosity as carriers will lead to poor hydrophilicity of the powder and reduced flavonoid dissolution. Therefore, under the conditions of Example 8, the total flavonoid release rate of oligofructose with lower viscosity is the highest (about 90%).

[0046] Embodiment 11

[0047] To a 600 mL polytetrafluoroethylene resonance cavity, 1.0 g of daylily powder, 1.0 g of oligofructose, 0.05 g of microcrystalline cellulose, and 15 mm diameter zirconia balls were added, and the mass ratio of microspheres to powder was set to 8:1. The mixture was treated at 30 Hz for 30 min. After treatment, the composite powder was taken out, 1 g of the composite micropowder was accurately weighed, 10 mL of water was added, and the mixture was stirred at room temperature for 30 min. The extraction process was repeated 3 times, and the filtrates were combined for 3 times. The total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water were calculated according to the method described in Example 1, and then the release rate of flavonoids in the daylily nano-composite micropowder was calculated.

[0048] Example 12

[0049] To a 600 mL polytetrafluoroethylene resonance cavity, 1.0 g of daylily powder, 1.0 g of oligofructose, 0.05 g of silica gel powder, and 15 mm in diameter of zirconium oxide balls were added, and the mass ratio of microspheres to powder was set to 8:1. The mixture was treated at 30 Hz for 30 min. After treatment, the composite powder was taken out, 1 g of the composite micropowder was accurately weighed, 10 mL of water was added, and the mixture was stirred at room temperature for 30 min. The extraction process was repeated 3 times, and the filtrates were combined for 3 times. The total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water were calculated according to the method described in Example 1, and then the release rate of flavonoids in the daylily nano-composite micropowder was calculated.

[0050] like Figure 1 As shown in B, adding hydroxypropyl cellulose as a disintegrant has the best effect. Since hydroxypropyl cellulose has good hydrophilicity, it can increase the hydrophilicity of the powder, so the dissolution is increased.

[0051] Embodiment 13

[0052] Take the daylily powder and grind it into ultrafine powder, take 1.0g of freeze-dried daylily ultrafine powder, add 1.0g of oligofructose and 0.05g of hydroxypropyl cellulose, and mix. Accurately weigh 1g of the physical mixture, add 10mL of water, stir for 30min at room temperature, filter, repeat this extraction process 3 times, combine the filtrates of 3 times, calculate the release rate of flavonoids in the sample according to the method described in Example 1, and use it as a control for subsequent pharmacological experiments and property studies.

[0053] Embodiment 14

[0054] The effect of the addition amount of oligofructose as an auxiliary material on the dissolution rate of flavonoids in daylily is preferred: add daylily powder to 600mL of polytetrafluoroethylene resonance cavity and control the addition amount of oligofructose to 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% of the total mass, the total mass of the composite (daylily powder and auxiliary materials) is 2.0g, 0.05g of hydroxypropyl cellulose, 15mm diameter zirconium oxide balls, set the mass ratio of microspheres to powder to 8:1, treat at 30Hz for 30min, take out the composite powder after treatment, accurately weigh 1g of composite micropowder, add 10mL of water, stir at room temperature for 30min, filter, repeat this extraction process 3 times, combine the filtrates of 3 times, calculate the total flavonoids in the composite micropowder and the flavonoids in the filtrate after dissolution with water according to the method described in Example 1, and then calculate the release rate of flavonoids in daylily nano-composite micropowder. Figure 1 The results of experiment C in Figure 1 show that as the amount of oligofructose increases, the release rate of daylily flavonoids increases slowly. However, excessive oligofructose dilutes the active ingredients of the product, leading to an increase in usage. Therefore, the preferred amount of oligofructose added here is 50% of the total mass.

[0055] Embodiment 15

[0056] Effect of the amount of disintegrant added on the dissolution rate of flavonoids from daylily: 1.0 g of daylily powder, 1.0 g of oligofructose, 0.01 g (0.5% disintegrant), 0.02 g (1% disintegrant), 0.05 g (2.5% disintegrant), 0.1 g (5% disintegrant), 0.2g (10% disintegrant dosage), 15mm diameter zirconium oxide balls, set the mass ratio of microspheres to powder to 8:1, treat at 30Hz for 30min, take out the composite powder after treatment, accurately weigh 1g composite micropowder, add 10mL water, stir at room temperature for 30min, filter, repeat this extraction process 3 times, combine the 3 filtrates, calculate the total flavonoids in the composite micropowder and the flavonoids in the filtrate after dissolution with water according to the method described in Example 1, and then calculate the release rate of flavonoids in the daylily nanocomposite micropowder. Figure 1 The results of experiment D in the figure show that as the amount of disintegrant increases, the release rate of daylily flavonoids increases and tends to be flat. When the amount of disintegrant reaches 1.0-2.5% of the composite powder, it has a good effect of increasing release and reducing agglomeration. Therefore, the preferred amount of hydroxypropyl cellulose is 2.5% of the total amount (i.e. 0.05g).

[0057] Example 16

[0058] Effect of the diameter of the preferred treatment beads on the dissolution rate of flavonoids from daylily: add 1.0 g of daylily powder, 1.0 g of oligofructose, 0.02 g of hydroxypropyl cellulose, and zirconium oxide balls with diameters of 10 mm, 15 mm, 20 mm, and 25 mm to a 600 mL polytetrafluoroethylene resonance cavity, set the mass ratio of microspheres to powder to 8:1, and treat at 30 Hz for 30 min. After treatment, take out the composite powder, accurately weigh 1 g of the composite micropowder, add 10 mL of water, stir at room temperature for 30 min, filter, repeat this extraction process 3 times, combine the filtrates of the 3 times, and calculate the total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water according to the method described in Example 1, and then calculate the release rate of flavonoids in the daylily nano-composite micropowder. Figure 2 The results of experiment B in the figure show that the infrasound-induced medium vibration generates additional strong mechanical force, the size of which is affected by the mass of the medium and the space in which the medium operates. Therefore, as the diameter of the microbeads used increases, the infrasound resonance effect increases significantly and the release rate rises. When the bead diameter is greater than 15 mm, the release rate of daylily flavonoids decreases significantly due to the limitation of the jar space and the reduction of the effective movement space. Therefore, a 15 mm medium is preferred.

[0059] Embodiment 17

[0060] The effect of the ratio of microspheres to powder on the dissolution rate of flavonoids in daylily: add 1.0 g of daylily powder, 1.0 g of oligofructose, 0.02 g of hydroxypropyl cellulose, and 15 mm diameter zirconium oxide balls to a 600 mL polytetrafluoroethylene resonance cavity, and control the mass ratio of microspheres to micropowder to be 1:1, 2:1, 5:1, 8:1, 10:1, and 20:1. Treat at 30 Hz for 30 min. After treatment, take out the composite powder, accurately weigh 1 g of composite micropowder, add 10 mL of water, stir at room temperature for 30 min, filter, repeat this extraction process 3 times, combine the filtrates of 3 times, and calculate the total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water according to the method described in Example 1, and then calculate the release rate of flavonoids in the daylily nano-composite micropowder. Figure 2 The results of experiment A in the figure show that as the ratio of microspheres to powder increases, the ball mass is larger and the force is applied more frequently under the same force, providing a higher total energy, so the release rate increases. However, when the ratio of microspheres to powder is further increased, the force application capacity is reduced due to the limitation of the resonance cavity space, so the release rate decreases. Therefore, the optimal ratio of microspheres to powder is 10:1.

[0061] Embodiment 18

[0062] The effect of the preferred infrasonic frequency on the dissolution rate of flavonoids in daylily: add 1.0g daylily powder, 1.0g oligofructose, 0.02g hydroxypropyl cellulose, and 15mm diameter zirconium oxide balls to a 600mL polytetrafluoroethylene resonance cavity, set the mass ratio of microspheres to powder to 10:1, and treat at 5Hz, 10Hz, 15Hz, 20Hz, 25Hz, 30Hz, 35Hz, 40Hz for 30min. After treatment, take out the composite powder, accurately weigh 1g of composite micropowder, add 10mL of water, stir at room temperature for 30min, filter, repeat this extraction process 3 times, combine the filtrates of 3 times, calculate the total amount of flavonoids in the composite micropowder and the amount of flavonoids in the filtrate after dissolution with water according to the method described in Example 1, and then calculate the release rate of flavonoids in the daylily nano-composite micropowder. Figure 2 The experimental results of C in show that as the infrasonic frequency increases, the number of resonances provided at the same force is more frequent and the total energy provided is higher, so the release rate increases. However, when the frequency is further increased, some impacts generate more heat, causing the loss of sensitive components such as flavonoids, so the release rate decreases. Therefore, the optimal infrasonic frequency is 30 Hz.

[0063] Embodiment 19

[0064] Effect of optimal treatment time on dissolution rate of flavonoids from daylily: add 1.0g daylily powder, 1.0g oligofructose, 0.02g hydroxypropyl cellulose, and 64 zirconia balls with a diameter of 15 mm to a 600mL polytetrafluoroethylene resonance cavity, set the mass ratio of microspheres to powder to 10:1, and treat at 30 Hz for 5min, 10min, 15min, 30min, 60min, and 120min. After treatment, take out the composite powder, accurately weigh 1g of composite micropowder, add 10mL of water, stir at room temperature for 30min, filter, repeat this extraction process 3 times, combine the filtrates of 3 times, and calculate the total flavonoids in the composite micropowder and the flavonoids in the filtrate after dissolution with water according to the flavonoid standard curve, and then calculate the flavonoid content in the aqueous solution. Figure 2 The results of experiment D in Figure 2 show that as the processing time increases, the total energy provided is higher, so the release rate increases. However, since the release rate of daylily flavonoids has reached the maximum content, the release rate of flavonoids has not changed significantly after processing for more than 30 minutes. Therefore, the optimal processing time is 30 minutes.

[0065] Embodiment 20

[0066] 1.0 g of daylily powder, 1.0 g of oligofructose, 0.02 g of hydroxypropyl cellulose, and 64 zirconia balls with a diameter of 15 mm were added to a 600 mL polytetrafluoroethylene resonance cavity. The mass ratio of microspheres to powder was set to 10:1. The mixture was treated at 30 Hz for 30 min. After treatment, the composite powder was taken out, 1 g of composite micropowder was accurately weighed, 10 mL of water was added, and the mixture was stirred at room temperature for 30 min. The extraction process was repeated 3 times, and the filtrates were combined. The total flavonoid content in the composite micropowder and the flavonoid content in the filtrate after dissolution with water were calculated according to the flavonoid standard curve, and then the flavonoid concentration in the aqueous solution was calculated. The experiment was repeated 3 times, and the flavonoid release rate was calculated to be 86.62 ± 0.23%.

[0067] Embodiment 21

[0068] Dissolution test of flavonoids in daylily composite micropowder: The dissolution apparatus used was Agilent Technologies 708-DS, with a paddle speed of 150 rpm, a dissolution medium of 900 mL of pH 6.8 phosphate buffer solution (simulated intestinal fluid), and a dissolution temperature of 37 ± 0.5 oC. Example 20 and Example 13 equivalent to 1 g of day lily were evenly sprinkled on the liquid surface. 3 mL of sample was extracted at preset time intervals (5 min, 10 min, 20 min, 40 min, 60 min, 80 min and 120 min), and an equal amount of fresh dissolution medium was added to the dissolution container. The collected samples were filtered through a 0.45 μm membrane filter. The flavonoid release rate of the samples was analyzed using the method of Example 1. Three parallel experiments were performed for each sample. Figure 3 As shown, compared with Example 13, Example 20 has significantly improved flavonoid release performance in a phosphate buffer solution with a pH value of 6.8. In the first 5 minutes, the flavonoid release rate was 46%, which increased to 77% within 20 minutes. After 60 minutes, the cumulative release rate was 86%, reaching the final release amount, while the release rate of the physical mixture of Example 13 was only about 55%.

[0069] Embodiment 22

[0070] The microscopic morphology of Example 20 and freeze-dried daylily powder was observed using a scanning electron microscope. The samples were observed using a Hitachi S-4700 scanning electron microscope under vacuum conditions and an accelerating voltage of 15.0 kV ( Figure 4 , Figure 4 A is freeze-dried daylily powder, and B is the composite micropowder prepared in Example 20). The scanning electron microscope of the original daylily powder can be observed to have many regular block structures and highly rough surfaces. The scanning electron microscope image of the powder prepared in Example 20 shows that most of the particle sizes of the obtained powder are significantly reduced, even reaching nano-scale micropowders of about 100 nm, and the cell walls of the daylily are almost completely destroyed. Through the resonance treatment of infrasound, the cell walls are crushed by strong squeezing and shearing forces. Therefore, the substances in the cells are easily released and dispersed, and can also be combined with the excipients under the action of mechanical force to form water-soluble supramolecular aggregates. The dissolution rate of the biologically active substances is improved, thereby enhancing its efficacy after oral administration.

[0071] Embodiment 23

[0072] Zebrafish tolerance dose study of Example 20: 180 5dpf wild-type AB strain zebrafish were randomly selected in a 6-well plate, and 30 zebrafish were treated in each well (experimental group). The raw materials of Example 20 were dispersed in water and administered respectively. According to the content of daylily, the concentrations were set to 7.5μg / mL, 15μg / mL, 30μg / mL, 60μg / mL, 90μg / mL, 120μg / mL and 240μg / mL. After 24h treatment at 28℃, the toxic reactions and deaths of zebrafish in each experimental group were observed and counted (Table 1). According to the results, the three dosing doses used in subsequent animal experiments were set to 15μg / mL (low dose), 30μg / mL (medium dose), and 60μg / mL (high dose).

[0073] Table 1 Zebrafish mortality

[0074]

[0075] Embodiment 24

[0076] Study on the antidepressant activity of Example 20: The experiment was divided into 9 experimental groups (Example 13 and Example 20 groups, high, medium and low dosages), a blank group, a model group and a positive control group. 270 5dpf wild-type AB strain zebrafish were randomly selected in a 6-well plate, and 30 zebrafish were treated in each well (experimental group). Experimental group 1 and experimental group 2 were respectively given the extraction solution of the micropowder of Example 20 (the concentration was converted to the content of daylily powder therein) and Example 13 (the concentration was converted to the content of daylily powder therein) in water, and the concentration of the daylily contained in the example was 15.00μg / mL, 30.00μg / mL and 60.00μg / mL, respectively, and the positive control group was sertraline 0.170 μg / mL. At the same time, a normal control group and a model control group were set up, and the capacity of each well was 3 mL. Except for the normal control group, the remaining experimental groups were given reserpine in water to establish a zebrafish depression model. After 24 hours of treatment at 28℃, the samples were washed with fish water. Eight zebrafish were randomly selected from each experimental group and data was collected for 10 minutes using a behavior analyzer. The total movement time of the zebrafish per minute in the bright field was analyzed, and the antidepressant efficacy of the samples was evaluated based on the statistical analysis results of this indicator. Figure 5As shown, both Example 13 and Example 20 have antidepressant activity at high concentrations, and the bright field movement time of zebrafish increases. Further investigation found that Example 20 can still achieve a good antidepressant effect at the lowest dose of 15.00 μg / mL, and the effect is close to that of Example 13 at 60 μg / mL, while the antidepressant effect of Example 13 at the same concentration is significantly weakened, indicating that the processing method of Example 20 improves the dissolution rate of flavonoids, which can significantly improve the antidepressant efficacy of the raw material, with less intake and better effect, and its antidepressant effective dose is more than 4 times higher than that of ultra-fine daylily powder.

[0077] Embodiment 25

[0078] Study on the intestinal excretion promoting activity of Example 20: The experiment was divided into 6 experimental groups (normal group (blank group, no drug administration), positive control group, Example 20 group (two high and low concentrations), Example 13 group (two high and low concentrations), 180 5dpf wild-type AB strain zebrafish were randomly selected in a 6-well plate, and 30 zebrafish were treated in each well (experimental group), and Nile red was administered in water to fill the gastrointestinal tract. Example 20 (converted according to the actual content of daylily) and Example 13 (converted according to the content of daylily) were administered in water at concentrations of 15μg / mL and 60μg / mL, respectively, and domperidone was 50.0μg / mL as a positive control. At the same time, a normal control group was set up, and the volume of each well was 3mL. After treatment at 28°C for 24h, 10 zebrafish were randomly selected from each experimental group and photographed under a fluorescence microscope. NIS-ElementsD3.20 advanced image processing software was used to collect data, and the zebrafish intestinal fluorescence intensity S (in pixels) was analyzed. The experimental results are shown as follows: Figure 6 According to the experimental conclusion, the data were further statistically processed to evaluate the intestinal motility promoting effect of each group. The formula used in the study to calculate the intestinal motility promoting effect is as follows:

[0079]

[0080] Depend on Figure 6 As known, Example 20 can promote intestinal peristalsis well at both high and low concentrations, and is even better than the control effect. The calculation results show that Example 20 has an intestinal motility-promoting effect of 62% and 88% in the freeze-dried daylily powder 15μg / mL and 60μg / mL concentration groups, respectively. However, Example 13 only showed a good intestinal motility-promoting effect at a high concentration of 60μg / mL, which was only 66%, and the effect was very mild at low concentrations, only 33%. This shows that the effective concentration of Example 20 in promoting intestinal motility is significantly better than that of Example 13, indicating that Example 20 has a more obvious intestinal motility-promoting effect under the experimental conditions, which fully illustrates the improvement in efficacy brought about by processing technology and solid-phase inclusion.

Claims

1. A method for preparing a daylily nanocomposite powder with a high flavonoid release rate, characterized in that: The specific steps are as follows: fresh daylily is freeze-dried and then initially crushed to 100-200 meshes, freeze-dried daylily powder is mixed with auxiliary materials and disintegrants, and subjected to infrasonic resonance treatment using an acoustic resonance mixer, while microspheres are used as a force medium, and then large particles are removed by sieving to obtain daylily nanocomposite micropowder; The mass of auxiliary materials added accounts for 10% to 90% of the total mass of raw materials; The infrasound frequency of the acoustic resonance mixer is 10 ~ 40Hz; the processing time is 5-120min; The disintegrant is hydroxypropyl cellulose, and the added amount is 2.5% of the total mass of the raw materials; The material of the acoustic resonance mixer is polytetrafluoroethylene, and zirconium oxide microspheres are used as the force medium. The diameter of the zirconium oxide is 10 to 25 mm, and the mass ratio of the microspheres to the powder is 1:1 to 20:

1.

2. The method for preparing the daylily nanocomposite powder with high flavonoid release rate as claimed in claim 1, characterized in that: The auxiliary materials are beta-cyclodextrin, maltodextrin, arabinogalactan, pectin, maltitol, erythritol, oligofructose, inulin, corn starch or sweet potato starch.

3. The method for preparing the daylily nanocomposite powder with high flavonoid release rate as claimed in claim 2, characterized in that: The auxiliary material is oligofructose.

4. The method for preparing the daylily nanocomposite powder with high flavonoid release rate according to claim 1, characterized in that: The mass of auxiliary materials added accounts for 50% of the total mass of raw materials.

5. The method for preparing the daylily nanocomposite powder with high flavonoid release rate according to claim 1, characterized in that: The diameter of the zirconium oxide was 15 mm, the mass ratio of the microspheres to the powder was 10:1, the infrasonic frequency of the acoustic resonance mixer was 30 Hz, and the treatment time was 30 min.

Citation Information

Patent Citations

  • Preparation method of plant extract dry powder

    CN113287747A